Penyuluhan Gizi Seimbang Melalui Media Podcast Sebagai Upaya Pencegahan Malnutrisi di Purwokerto - Adinna Islah Perwita; Prita Suci Nurcandrani (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2026)
Malnutrition is a condition of deficiency or excess of nutrients. This malnutrition is caused by various factors, including a lack of public nutrition literacy. Therefore, to prevent cases of malnutrition in Purwokerto, balanced nutrition education is being conducted thru podcast media. This medium was chosen so that it could provide audio-visual education and be accessed repeatedly and widely. The podcast creation process consists of pre-production, production, and post-production. This educational activity is in collaboration with a nutritionist from the Purwokerto Utara 2 Public Health Center. The results of views and interactions such as likes indicate positive feedback from the audience, even if it's limited. This indicates that a digital media-based approach, particularly podcasts, can be an effective means of supporting the dissemination of nutritional information and raising public awareness about the importance of a healthy diet.